Mental health risk communication and community participation among an Indigenous people in Colombia - Felipe Agudelo-Hernández; Lizeth Paola Coral-Vela; Luz Helena Pabuena-Yepes (Revista Panamericana de Salud Pública)
Objectives. To describe and analyze a community participation process to develop recommendations for adequate communication of mental health risks among the Wayuú people of Colombia. Methods. This qualitative study conducted focus groups in the Indigenous cities of Albania and Uribia, Colombia, from January to June 2024, to assess perspectives on mental health risk communication. Participants were adults (>18 years) residing in two municipalities in La Guajira (Uribia and Albania [the Indigenous capital of Colombia]) and included youth group leaders, Indigenous representatives, migrant population representatives, and representatives of official institutions in the region. Thematic analysis was used for data analysis. Results. In total, 42 participants (mean [SD] age, 20.1 years; 24 [57.1%] women and 18 [42.9%] men) participated in four focus groups (two in Albania and two in Uribia). Three main themes were identified in the thematic analysis: consequences of poor communication; community advice for social communication; and recommendations for public mental health in health communication. Based on the data analysis, recommendations for mental health risk communication were proposed for both municipalities and for the territory of La Guajira, Colombia. Conclusions. The findings of this qualitative study highlight the need to improve mental health communication among the Indigenous community by leveraging their perspectives. The involvement of community leaders and the development of mental health communication strategies are needed.